AI is transforming how science is done. Science education must reflect this change. - Erduran, S (American Association for the Advancement of Science, 2023)
There is growing interest in the use of artificial intelligence (AI) in science education. Many issues and questions raised about the role of AI in science education target primarily science learning objectives. They relate to AI's capacity to generate tools for teaching, learning, and assessment, as well as the advantages and disadvantages of using such tools. But another important discussion receiving far too little attention in science education concerns how AI is transforming the nature of science (NOS) itself and what such transformation implies for the education of young children. For education, it is critical to ask what AI-informed NOS is, what skills it demands of learners, and how schools can aim to achieve them.